Assessing the Safety of Polymeric Nanoparticulated Systems developed for Drug Delivery with Human Osteoblasts - Dias, Kamila (2019)
The development of novel nanocarriers has been recognized as a promising approach to improve drug release profiles within the target sites, being the assessment of their biocompatibility and safety a critical point of the process. For this purpose, Poly(methyl methacrylate) (PMMA) and PMMA-Eudragit RL 100 (PMMA-Eud, 50:50) nanoparticles (NPs) were recently produced to target bone infections following prosthetic surgeries and a first toxicity screening on fibroblats was conducted. The objective of the present work was to further characterize the cellular interactions and the potential toxicity of those polymeric NPs, using human osteoblasts. PMMA and PMMA-Eud (50:50) NPs were produced by single emulsion evaporation methodology and their physicochemical properties (size distribution, surface charge, morphology and aggregation/agglomeration states) were assessed. Their safety was evaluated both in normal and differentiated MG63 cells through studies of cell uptake, cyto- and genotoxicity using several endpoints: cell viability, oxidative stress production, DNA and chromosome damage. The successful cellular uptake of PMMA and PMMA-Eud by osteoblast was confirmed. None of the NPs was cytotoxic or induced oxidative stress in differentiated cells, although a moderated toxicity was detected in undifferentiated cells. As to the genotoxic potential, both NPs induced primary DNA damage detected by the comet assay, especially in short-term exposure. Noteworthy, none of the NPs caused chromosome breakage/loss using the micronucleus assay that is recommended by OECD/ICH testing guidelines for pharmaceuticals. Our findings suggest that, despite PMMA and PMMA-Eud are promising nanocarriers for drug delivery, the primary genotoxicity observed in osteoblasts needs to be further investigated. In addition, the fact that NPs affect differently normal and differentiated osteoblasts suggests the need of using more sophisticated in vitro cellular systems to better mimic the complexity of the target tissues and thus minimize the utilization of in vivo models.